Functional characterisation and antimicrobial efficiency assessment of smart nanohydrogels containing natamycin incorporated into polysaccharide-based films - Fuciños, C. (2015)
The potential application of polysaccharide-based films containing smart nanohydrogels for the controlled release of food preservatives is demonstrated here. Smart active packaging is the most promising alternative to traditional packaging as it provides a controlled antimicrobial effect, which allows reducing the amount of preservatives in the food bulk, releasing them only on demand. This work evaluates the usefulness of smart thermosensitive poly(N-isopropylacrylamide) (PNIPA) nanohydrogels with or without acrylic acid (AA) incorporated into polysaccharide-based films (GA) to transport natamycin and release it as a response to environmental triggers. Release kinetics in liquid medium from GA films containing PNIPA/AA nanohydrogels (GA-PNIPA(5) and GA-PNIPA-20AA(5)) presented a characteristic feature regarding the films without nanohydrogels that was the appearance of a lag time in natamycin release, able to reach values of around 35 h. Another important feature of natamycin release kinetics was the fact that the release from GA-PNIPA/AA films only occurred when temperature was increased, so that the natamycin release was restricted to when there is a risk of growth of microorganisms that cause food spoilage or the development of pathogenic microorganisms. Additionally, it could be observed that the relative fraction of natamycin released from GA-PNIPA/AA films was significantly (p<0.05) higher than that released from GA films loaded with the same amount of free natamycin. It can be hypothesised that the encapsulation of natamycin into nanohydrogels helped it to be released from GA films, creating reservoirs of natamycin into the films and, therefore, facilitating its diffusion through the film matrix when the nanohydrogel collapses. In a solid medium, the low water availability limited natamycin release from GA-PNIPA/AA films restricting the on/off release mechanism of PNIPA/AA nanohydrogels and favouring the hydrophobic interactions between natamycin and polymer chains at high temperatures. Despite the low natamycin release in solid media, antimicrobial efficiency of GA-PNIPA(5) films containing natamycin in acidified agar plates was higher than that obtained with GA films without natamycin and GA films with free natamycin, probably due to the protecting effect against degradation when natamycin was included in the nanohydrogels, allowing its release only when the temperature increased.